2012
DOI: 10.1097/psy.0b013e31826aff0b
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Versus Long-Term Effects of Depressive Symptoms on Mortality in Patients on Dialysis

Abstract: Depressive symptoms at the start of dialysis therapy are associated with short-, medium-, and long-term mortality. The cause-specific mortality risk over time may help clinicians to understand multifactorial causes of the association between depressive symptoms and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…As part of the Dialysis Outcomes and Practice Patterns Study, Lopes et al demonstrated that among patients on chronic hemodialysis, depression was independently associated with increased mortality and hospitalization (15). Several other studies reported similar associations as well as lower medication and dietary adherence among patients on chronic hemodialysis with depression (16)(17)(18)(19)(20)(21)(22)(23)(24). Considerably less is known about the associations of pain with clinical outcomes, although a recent study found that interdialytic pain was associated with increased mortality (25).…”
Section: Introductionmentioning
confidence: 88%
“…As part of the Dialysis Outcomes and Practice Patterns Study, Lopes et al demonstrated that among patients on chronic hemodialysis, depression was independently associated with increased mortality and hospitalization (15). Several other studies reported similar associations as well as lower medication and dietary adherence among patients on chronic hemodialysis with depression (16)(17)(18)(19)(20)(21)(22)(23)(24). Considerably less is known about the associations of pain with clinical outcomes, although a recent study found that interdialytic pain was associated with increased mortality (25).…”
Section: Introductionmentioning
confidence: 88%
“…[9][10][11][12] Frailty and depression have been separately associated with higher mortality in dialysis and nondialysis populations. 1,5,[13][14][15] Among nondialysis populations, the simultaneous presence of both conditions is associated with even poorer outcomes than the presence of either condition alone. 3,16 However, the independent contributions of frailty and depression to poor outcomes have not been investigated in the hemodialysis population.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic dialysis patients are known for the presence of a chronic inflammatory state 1 and for a high prevalence of depressive symptoms 2 . Depressive symptoms are associated with morbidity and both short-term and long-term mortality in dialysis patients [3][4][5][6] . Also higher levels of inflammation markers (especially CRP) have been found to be associated with both higher morbidity and mortality 7-10 .…”
Section: Introductionmentioning
confidence: 99%